Neutrophil extracellular traps and its implications in inflammation: an overview - Delgado-Rizo, Vidal; Martínez-Guzmán, Marco A.; Iñiguez-Gutierrez, Liliana; García-Orozco, Alejandra; Alvarado-Navarro, Anabell; Fafutis-Morris, Mary (Frontiers in Immunology, 2017)
In addition to physical barriers, neutrophils are considered a part of the first line of immune defense. They can be found in the bloodstream, with a lifespan of 6-8 hours, and in tissue, where they can last up to seven days. The mechanisms that neutrophils utilize for host defense are phagocytosis, degranulation, cytokine production and, the most recently described, neutrophil extracellular trap (NET) production. NETs are DNA structures released due to chromatin decondensation and spreading, and they thus occupy 3-5 times the volume of condensed chromatin. Several proteins adhere to NETs, including histones and over 30 components of primary and secondary granules, among them components with bactericidal activity such as elastase, myeloperoxidase, cathepsin G, lactoferrin, pentraxin 3, gelatinase, proteinase 3, LL-37, peptidoglycan-binding proteins and others with bactericidal activity able to destroy virulence factors. Three models for NETosis are known to date. a) Suicidal NETosis, with a duration of 2-4 hours, is the best described model. b) In vital NETosis with nuclear DNA release, neutrophils release NETs without exhibiting loss of nuclear or plasma membrane within 5-60 minutes, and it is independent of ROS and the Raf/MERK/ERK pathway. c). The final type is Vital NETosis with release of mitochondrial DNA that is dependent on ROS and produced after stimuli with GM-CSF and LPS. Recent research has revealed neutrophils as more sophisticated immune cells that are able to precisely regulate their granular enzymes release by ion fluxes and can release immunomodulatory cytokines and chemokines that interact with various components of the immune system. Therefore, they can play a key role in autoimmunity and in autoinflammatory and metabolic diseases. In this review, we intend to show the two roles played by neutrophils: as a first line of defense against microorganisms and as a contributor to the pathogenesis of various illnesses, such as autoimmune, autoinflammatory and metabolic diseases.